Penerapan Model Pembelajaran Aktif Tipe Every One is a Teacher Here Pada Materi ”Meraih Kesuksesan” untuk Meningkatkan Hasil Belajar Peserta Didik di Kelas X1 SMAN 13 Luwu - Qalbi H, M. Raehan; Iman, Bustanul; Fakhrunnisaa, Nur (Indo-MathEdu Intellectuals Journal, 2026)
This study aimed to improve students’ learning outcomes through the implementation of the active learning model Everyone Is A Teacher Here on the topic “Achieving Success” in class X1 of SMAN 13 Luwu. This research employed Classroom Action Research (CAR) based on the Hopkins model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 32 students. Data were collected through tests, observations, interviews, and documentation. Data analysis was conducted using quantitative and qualitative approaches by calculating the mean scores and learning mastery percentages. The findings indicated a significant improvement from Cycle I to Cycle II. In Cycle I, the average score was 68 with 41% learning mastery, while in Cycle II the average increased to 78 with 78% mastery. The implementation of the Everyone Is A Teacher Here model enhanced students’ participation, confidence, and engagement, which positively impacted their learning outcomes. This model proved effective in creating an interactive and participatory Islamic Education learning environment.